2017
DOI: 10.1590/s0100-204x2017001200017
|View full text |Cite
|
Sign up to set email alerts
|

Root dry matter mass and distribution of Florico grass under different grazing strategies

Abstract: The objective of this work was to evaluate the variations in root dry matter mass (RDM) and the percentage distribution (PD) of the root density of Florico grass (Cynodon nlemfuensis) in the 0-40-cm soil layer, when managed under different grazing strategies. Two defoliation frequencies (90 and 95% light interception, as the criterion for allowing animals in the paddock) and two defoliation severities (post-grazing heights of 20 or 30 cm) were assessed. Four seasonal evaluations of the root system were perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…The distribution of roots in the soil profile is consistent with results published by several authors [33][34][35], who reported root concentrations of forage grasses always being higher than 50% in the layer of 0 to 10 cm.…”
Section: Root Systemsupporting
confidence: 91%
“…The distribution of roots in the soil profile is consistent with results published by several authors [33][34][35], who reported root concentrations of forage grasses always being higher than 50% in the layer of 0 to 10 cm.…”
Section: Root Systemsupporting
confidence: 91%
“…The balance between the shoot and root dry weight in the seedlings from cuttings with 3 buds led to the best investment in roots and improved the seedling quality. This relationship is of fundamental importance for the organization and functioning of the physiological processes and for plant development, where the root is the energy source and the aerial part is a drain on the organic reserves (Barros et al, 2017).…”
Section: Development Of Nursery Seedlingsmentioning
confidence: 99%